A preliminary comparison of leadership practices at select educational NGOs in Indonesia, Tanzania, and Kyrgyzstan: probing into challenges and possibilities - Paramboor, Jafar (2024)
The present paper delves into the landscape of leadership practices at educational NGOs within the contexts of three countries. Specifically, the aim of this scholarly investigation is to identify the existing practices in leadership at selected NGO institutions working for educational empowerment in these three countries and highlight the limitations as well as the possibilities of leadership across the institutions. The paper also looks into how the leadership is contextualized in these areas, by critically analyzing and comparing the three leadership contexts. Data were obtained from those in leadership positions at 14 NGOs in Indonesia, seven NGOs from Kyrgyzstan, and 16 NGOs from Tanzania. Various strategies were employed including interviews, survey instruments, observations, and standardized assessment tool kits prepared by the NAMA Foundation. The collected data is filtered and scrutinized through qualitative data analysis techniques, including thematizing the responses and later relating all the available themes to the relevant leadership theories. This helped in identifying the multi-faceted challenges in the prevailing practices at the educational NGOs of these three countries. The findings of this study have revealed the complex interplay between the NGO leadership, organizational outcomes, and the effectiveness of their educational endeavors.